2008
DOI: 10.1177/0192623308326093
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profile of Clinical Signs and Histopathologic Changes in an F-344 Rat Model of Kainic Acid–induced Mesial Temporal Lobe Epilepsy

Abstract: Since there is limited information in the literature, the purpose of this study was to investigate clinical signs, morphology, and temporal progression of lesions from Days 3 to 168 in a kainic acid (KA)-induced Fischer-344 (F-344) rat model of mesial temporal lobe epilepsy (MTLE). Following a single KA subcutaneous dose of 9 mg/kg to young adult male rats, 95% survived, 93% exhibited status epilepticus, and 80% eventually developed spontaneous motor seizures. Histopathology included hematoxylin and eosin (H&E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 79 publications
(94 reference statements)
3
37
1
Order By: Relevance
“…5 In rodent models of this condition, abnormal hippocampal neurogenesis has been found in adult animals, and these new-born neurons are predominantly in ectopic hilar regions but also in the dentate granule cell layer. 8,10,13,14 Similar observations have been reported in children. 3 It is now widely accepted that neurogenesis occurs under physiological conditions in adult mammals, especially in the dentate gyrus of the hippocampus and the subventricular zone of lateral ventricles.…”
supporting
confidence: 86%
“…5 In rodent models of this condition, abnormal hippocampal neurogenesis has been found in adult animals, and these new-born neurons are predominantly in ectopic hilar regions but also in the dentate granule cell layer. 8,10,13,14 Similar observations have been reported in children. 3 It is now widely accepted that neurogenesis occurs under physiological conditions in adult mammals, especially in the dentate gyrus of the hippocampus and the subventricular zone of lateral ventricles.…”
supporting
confidence: 86%
“…The mechanisms by which rapamycin produces these positive effects, however, are unclear. For the present study, we examined several hippocampal abnormalities implicated in the development of temporal lobe epilepsy (Parent and Kron, 2012; Hester and Danzer, 2014), including mossy fiber sprouting (Buckmaster, 2014), hilar ectopic granule cell accumulation (Scharfman and Pierce, 2012), basal dendrite formation (Ribak et al, 2012), reactive astrogliosis and microgliosis (Sharma et al, 2008; Gibbons et al, 2013) and mossy cell loss (Jinde et al, 2013). Consistent with previous studies (Zeng et al, 2009; Buckmaster et al, 2009), we observed a significant reduction in mossy fiber sprouting with rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On days 14 and 28, hippocampi were collected for gene array from only those rats that developed spontaneous motor seizures. In the companion study (Sharma et al 2008), histopathological changes relevant to the categories of neuronal degeneration, aberrant mossy fiber sprouting, microgliosis, and astrogliosis were recorded at days 3, 6, 14, and 28. Severity scores for each of the categories at each time point were generated and are shown in Figure 1.…”
Section: Behavioral and Histopathological Observationsmentioning
confidence: 99%
“…To obtain a better understanding of the underlying molecular mechanisms and identify potential biomarkers of lesion progression, we used a rat kainic acid (KA) treatment model of MTLE coupled with global gene expression analysis to examine temporal (four hours, days 3, 14, or 28) gene regulation relative to hippocampal histopathological changes. The authors recommend reviewing the companion histopathology paper (Sharma et al 2008) to get a better understanding of the work presented here. Analysis of filtered gene expression data using Ingenuity Pathways Analysis (Ingenuity Systems, http://www.ingenuity.com) revealed that a number of genes pertaining to neuronal plasticity (RhoA, Rac1, Cdc42, BDNF, and Trk), neurodegeneration (Caspase3, Calpain 1, Bax, a Cytochrome c, and Smac/Diablo), and inflammation/immune-response pathways (TNF-a, CCL2, Cox2) were modulated in a temporal fashion after KA treatment.…”
mentioning
confidence: 99%